The Effect of Health Service Quality on Outpatient Satisfaction at the Buluspesantren Health Center - Dimas Pramudya; Fitri Wulandari; Teguh Kusriyadi (Budapest International Research and Critics University, 2021)
Service quality is an assessment of a service provided to the public. With respect to good service quality, consumers will continuously re-consumption due to the satisfaction they feel. Thus, good service quality will lead to satisfaction. While the data collection techniques used are interviews, observations. The results showed that the quality of health services was good quality data for 18 outpatients (60%) and poor quality data for 12 outpatient data (40%). While patient satisfaction was 16 patients (53.3%) and 14 patients were less satisfied (46.7%). The results of the T-test obtained a significance value of <0.5, meaning that H1 is accepted, which means that it is contained in the quality of health services to outpatient satisfaction. It is concluded that the quality of health services has an influence on patient satisfaction.